Determinasi Jaminan Layanan dan Perceived Quality terhadap Kepuasan Konsumen Pengguna Jasa Bengkel Honda AHASS 0501 - Ilfam Yaksi; Kokom Komariah; Asep M. Ramdan (Journal of Management and Bussines (JOMB), 2019)
The purpose of this study was to determine the effect of collateral and perceived quality on consumer satisfaction at AHASS 0501. Workshop This research method uses the type of sampling included in the random sampling sample. The analysis technique used is multiple linear analysis techniques, and for testing the hypothesis is a simultaneous test (f test). Based on the coefficient of determination test of 0.868 can be interpreted that the effect of service assurance and perceived quality on customer satisfaction is 75.3%. The remaining 24.7% is influenced by other factors not explained in this study. Based on the f test, a probability value of sig is obtained. 0,000 <0.05 and the F test calculation shows that the F count is greater than the F table which is 129,777> 2.37. Conclusions, Service Guarantee (X1) and Perceived Quality (X2) have a significant effect on Consumer Satisfaction (Y). Keywords: Guarantee, Quality Perception, Consumer Satisfaction